Plasmodium matutinum Transmitted by Culex pipiens as a Cause of Avian Malaria in Captive African Penguins (Spheniscus demersus) in Italy - Iurescia, Manuela; Romiti, Federico; Cocumelli, Cristiano; Diaconu, Elena Lavinia; Stravino, Fiorentino; Onorati, Roberta; Alba, Patricia; Friedrich, Klaus Gunther; Maggi, Flavio; Magliano, Adele; Ermenegildi, Arianna; Carfora, Virginia; et al. (Frontiers in Veterinary Science, 2021)
-See uploaded manuscript